ISOLASI BAKTERI DARI RENDAMAN AKAR BAMBU DAN RESPON PEMBERIANNYA TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN TERUNG UNGU (Solanum melongena L.) - Hilwa Walida (JURNAL AGROPLASMA, 2019)
Soil microbes contained in bamboo roots are classified as Plant Growth Promoting Rhizobacteria (PGPR). PGPR is a soil microbe found in plant roots that can increase plant growth and protect certain pathogens. This aims of this study were to determine the diversity of bacterial isolates from bamboo root baths and the growth and production response of purple eggplant plants (Solanum melongena L.) with the application of biological fertilizers from bamboo root baths. This research was begun with making biological fertilizers from bamboo root baths. Furthermore, the biofertilizer was taken sufficiently to analyze the diversity of bacterial isolates in the laboratory. Each treatment was repeated 10 times, so that the experimental unit was observed as many as 40 plant samples. This study was analyzed descriptively by characterizing isolates and calculating the mean of each parameter. Based on the results of bacterial isolation from bamboo root baths, 8 isolates of bacteria were found with different macroscopic morphological characteristics including 7 Gram-positive bacterial isolates and 1 Gram-negative bacterial isolate and 5 bacillary (stem) isolates and 3 (round) coco isolates. The highest average in all parameters (plant height, number of leaves, leaf width and initial fruit weight) were in the M4 treatment (dose of 20 ml / plant). Keywords: Bacteria, Bamboo Root Baths, Solanum melongena L.